Epigenomics-based identification of oestrogen-regulated long noncoding RNAs in ER+ breast cancer. Issue 11 (1st November 2020) - Zhang, Zhao; Yu, Wei; Tang, Dan; Zhou, Yufan; Bi, Mingjun; Wang, Hu; Zheng, Yan; Chen, Mingqiu; Li, Li; Xu, Xinping; Zhang, Wei; Tao, Huimin; et al.
ABSTRACT: Breast cancer is one of the most prevalent cancers in women worldwide. Through the regulation of many coding and non-coding target genes, oestrogen (E2 or 17β-oestradiol) and its nuclear receptor ERα play important roles in breast cancer development and progression. Despite the astounding advances in our understanding of oestrogen-regulated coding genes over the past decades, our knowledge on oestrogen-regulated non-coding targets has just begun to expand. Here we leverage epigenomic approaches to systematically analyse oestrogen-regulated long non-coding RNAs (lncRNAs). Similar to the coding targets of ERα, the transcription of oestrogen-regulated lncRNAs correlates with the activation status of ERα enhancers, measured by eRNA production, chromatin accessibility, and the occupancy of the enhancer regulatory components including P300, MED1, and ARID1B. Our 3D chromatin architecture analyses suggest that lncRNAs and their neighbouring E2 -resonsive coding genes, exemplified by LINC00160 and RUNX1, might be regulated as a 3D structural unit resulted from enhancer-promoter interactions. Finally, we evaluated the expression levels of LINC00160 and RUNX1 in various types of breast cancer and found that their expression positively correlated with the survival rate in ER+ breast cancer patients, implying that the oestrogen-regulated LINC00160 and its neighbouring RUNX1 might represent potential biomarkers for ER+ breast cancers.